2003
DOI: 10.1016/s0167-7187(02)00146-7
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of strategic vertical separation and integration

Abstract: This paper gives conditions under which vertical separation is chosen by some upstream firms, while vertical integration is chosen by others in the equilibrium of a symmetric model. A vertically separating firm trades off fixed contracting costs against the strategic benefit of writing a (two-part tariff, exclusive dealership) contract with its retailer. Equilibrium coexistence emerges when observable and non-renegotiable contracts are offered to downstream Cournot oligopolists that supply close substitutes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…7,8 It fits nicely, however, with the 5 These papers include Ordover et al (1990), Abiru et al (1998), Elberfeld (2002, and Jansen (2003); see Section 6 for details.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…7,8 It fits nicely, however, with the 5 These papers include Ordover et al (1990), Abiru et al (1998), Elberfeld (2002, and Jansen (2003); see Section 6 for details.…”
mentioning
confidence: 67%
“…Employing yet another variant of the linear Cournot model, Elberfeld (2002) also obtains asymmetric integration equilibria in a symmetric setting, and he derives the conditions under which there is a negative relation between market size and the extent of vertical integration. Jansen (2003) provides conditions under which some (otherwise symmetric) upstream firms choose vertical integration, whereas others choose vertical separation, using a variant of a model proposed by Gal-Or (1990), where downstream demand is linear and firms competeà la Cournot. Ordover et al (1990) study a 2×2 firms model with price competition and differentiated downstream goods.…”
Section: Endogenous Asymmetric Equilibriamentioning
confidence: 99%
“…While game-theoretic work has demonstrated that asymmetric vertical market structure may arise endogenously (see, e.g., Ordover et al 1990, Elberfeld 2002, Jansen 2003, and Dufeu 2004, there is considerable debate about the robustness of this result. This is reflected in a recent paper by Buehler and Schmutzler (2005), who argue that there are good reasons why vertical integration decisions tend to be strategic substitutes, but also emphasize potential countereffects.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis is also related to the literature on the strategic delegation in a competitive environment. The idea that, in a full information framework, delegation can act as a strategic commitment device to relax competition traces back to Fershtman andJudd (1987), Sklivas (1987), Bonanno and Vickers (1988) and more recently Jansen (2003). In particular, Bonanno and Vickers (1988) find that in a differentiated good price competition model a manufacturer prefers to sell its product through an independent retailer rather than directly to consumers if it can publicly commit to a wholesale price above marginal costs, which induces a more lenient behavior of rivals.…”
Section: Related Literaturementioning
confidence: 99%